Photocatalytic degradation of dyes and pesticides in the presence of ions - Pete, Kwena Yvonne (My University, 2015)
Water pollution caused by organic and inorganic contaminants represents an important ecological and health hazard. Simultaneous treatment of organic and inorganic contaminants had gradually gained great scientific interest. Advanced oxidation processes such as photocatalysis, using TiO2 as a photocatalyst, have been shown to be very robust in the removal of biorecalcitrant pollutants. These methods offer the advantage of removing the pollutants, in contrast to conventional techniques. At present, the main technical challenge that hinder its commercialization remained on the post-recovery of the photocatalyst particles after water treatment. Supporting of the photocatalyst on the adsorbent surface is important as it assists during the filtration step, reducing losses of the materials and yielding better results in degrading pollutants. To overcome this challenge, in this study composite photocatalysts of TiO2/zeolite and TiO2/silica were prepared and investigated to explore the possible application in the simultaneous removal of organic and inorganic compounds from contaminated water. The main objective of this study was to investigate the heterogeneous photocatalytic degradation of organic compounds in the presence of metal ions using composite photocatalysts. The Brunauer–Emmett–Teller (BET), Scanning Electron Microscopy and Energy Dispersive X-ray (SEM-EDX), Raman spectroscopy (RS) and zeta potential (ZP) analyses were used to characterize the prepared composite photocatalysts. The successive composite photocatalysts were used in a semi-batch reactor under an irradiation intensity of 5.5 mW/m2 (protected by a quartz sleeve) at 25 ± 3°C for the photocatalytic degradation of synthetic textile (methyl orange) and agricultural (atrazine) wastewater in the presence of ions. The effect of operating parameters such as TiO2 composition on supporting material, particle size, composite photocatalyst loading, initial pollutant concentration and pH were optimized. The effects of inorganic salts and humic acid on dye and pesticides degradation were also studied, respectively. The performance of the photocatalyst reactor was evaluated on the basis of color removal, metal ion reduction, total organic carbon (TOC) reduction, intermediates product analysis and modeling of kinetics and isotherms. Different kinetic and isotherm models were introduced and applied in this work. Important aspects such as error functions with the optimal magnitude were used for the selection of the best suitable model.
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology
Keywords: Water pollution; Organic contaminants; Inorganic contaminants; Oxidation processes; Photocatalysis; Biorecalcitrant pollutants; Degrading pollutants; Agricultural wastewater; Dye degradation; Pesticide degradation; Kinetic models; Isotherm models; 628.166; Sewage -- Treatment; Water -- Purification; Environmental chemistry